2020
DOI: 10.1136/gutjnl-2020-322519
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Rome IV criteria with the Rome III criteria for the diagnosis of irritable bowel syndrome in secondary care

Abstract: ObjectivesDespite being proposed 4 years ago, there has been no independent validation study of the Rome IV criteria for IBS. We assessed their performance for the diagnosis of IBS in secondary care and compared them with the previous iteration, the Rome III criteria.DesignWe collected complete symptom data from consecutive adult patients with suspected IBS referred to a single UK clinic. All subjects underwent relatively standardised workup, with assessors blinded to symptom status. The reference standard use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 51 publications
(32 reference statements)
0
63
1
5
Order By: Relevance
“…In a patient with normal investigations from primary care on referral, exhibiting typical symptoms, and in the absence of alarm symptoms or signs, or atypical features, the diagnosis of IBS is secure (figure 1). A validation study of the Rome IV criteria in secondary care demonstrated this was particularly the case for IBS-C and IBS-M. 21 Patients meeting these criteria were 21 times more likely to have IBS-C than to not have IBS-C, and 11 times more likely to have IBS-M than to not have IBS-M after limited diagnostic workup. The clinician should, therefore, appear confident and, after clinical assessment is complete, communicate a positive diagnosis of IBS based on symptoms.…”
Section: Investigations In Secondary Carementioning
confidence: 98%
See 1 more Smart Citation
“…In a patient with normal investigations from primary care on referral, exhibiting typical symptoms, and in the absence of alarm symptoms or signs, or atypical features, the diagnosis of IBS is secure (figure 1). A validation study of the Rome IV criteria in secondary care demonstrated this was particularly the case for IBS-C and IBS-M. 21 Patients meeting these criteria were 21 times more likely to have IBS-C than to not have IBS-C, and 11 times more likely to have IBS-M than to not have IBS-M after limited diagnostic workup. The clinician should, therefore, appear confident and, after clinical assessment is complete, communicate a positive diagnosis of IBS based on symptoms.…”
Section: Investigations In Secondary Carementioning
confidence: 98%
“…19 The fall in prevalence in IBS that results from the changes made in moving from the Rome III to Rome IV criteria is noteworthy, reflecting the more restrictive nature of the latter. This has important clinical implications because, although as intended, the criteria are now more specific for diagnosing IBS, 21 up to 50% of patients who believe they have IBS will no longer meet criteria for the condition. Instead, they will be diagnosed as having another functional bowel disorder, 22 23 such as functional diarrhoea, functional constipation or functional abdominal bloating or distension.…”
Section: Epidemiologymentioning
confidence: 99%
“…It is characterised by a specific pattern of gastrointestinal symptoms, namely, altered stool form or frequency in association with abdominal pain, 1 and is diagnosed using the Rome criteria. These criteria have been revised three times since their inception, to make them more specific for diagnosing IBS, 2 and the latest iteration, Rome IV, was published in 2016 1 . Rome IV also redefined IBS as a disorder of gut–brain interaction, in recognition of the complex interplay between biological, psychological and social factors in its pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, confounding due to underlying differences between RCTs, including patient characteristics, IBS severity and diagnostic criteria over the 20‐year range these trials were conducted is possible. The Rome IV criteria are more specific than their predecessors, 73 but seem to select a group of patients with more severe symptoms and higher levels of psychological comorbidity 74 . Whether the findings of this study are applicable to those with Rome IV criteria IBS is unclear.…”
Section: Discussionmentioning
confidence: 79%